Medicina para além de “salvar vidas”: a formação de um estudante de medicina em uma narrativa crítico-reflexiva - Saraiva, Thalia Silva (Universidade Federal de São Carlos, 2024)
The present work is a critical-reflexive narrative about the training of a medical student. Graduating in medicine is a complex period, endowed with criteria and responsibilities that cause the student to face personal and interpersonal conflicts that generate anguish and suffering in the face of uncertainty about their ability to be a good doctor in the future. In the context of the pandemic, such feelings grew exponentially as medical internship came to a standstill. The present work aims to report the experience of a medical student before, during and after the COVID-19 pandemic and how the course influenced his life, his profession and mental health.
Medicine beyond “saving lives”: a medical student training in a critical-reflexive narrative
Keywords: Educação médica; Pandemia COVID-19; Saúde mental na medicina; Medical education; COVID-19 pandemic; Mental health in medicine; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA